Validity and reproducibility of a tool for assessing clinical competencies in physical therapy students 13 Education 1303 Specialist Studies in Education (2018)
Background: The evaluation of competencies in the clinical field is essential for health professionals, as it allows the acquisition of these competencies to be tracked. The objective of this study was to create and evaluate the validity and reliability of a tool for measuring clinical competencies in physical therapy (PT) students to assess the quality of their performance in a professional context. Methods: A descriptive study was designed. The Measurement Tool for Clinical Competencies in PT (MTCCP) was developed based on the evaluation of 39 experts: 15 clinicians and 24 instructors. The content validity was evaluated using the Content Validity Index (CVI). Three professors were invited to apply the tool to 10 students. Cronbach's alpha, exploratory factor analysis, and the intraclass correlation coefficient were used to determine the reliability and validity of the scale. Results: The CVI was positive - higher than 0.8. Principal component analysis confirmed the construct validity of the tool for two main factors: clinical reasoning (first factor) and professional behavior (second factor). With regard to reliability, the MTCCP achieved an internal congruence of 0.982. The inter-evaluator reproducibility for clinical reasoning, professional behavior, and the total MTCCP score was almost perfect; the ICCs were 0.984, 0.930, and 0.983, respectively. Conclusions: The MTCCP is a valid and reliable instrument for assessing the performance of PT students in hospital settings and can be used to determine what skills students feel less confident using and what additional training/learning opportunities could be provided. Further research is needed to determine whether the MTCCP has similar validity and reproducibility in other Spanish-speaking national and international PT programs. © 2018 The Author(s).